The Demand for Reinsurance: Theory and Empirical Tests - Garven, James R.; Tennant, Joan Lamm (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2003)
This paper investigates the valuation effects of reinsurance purchases in a contingent claims framework. The comparative statics of the model suggest that, other things equal, the demand for reinsurance will be greater, 1) the higher the firm’s leverage, 2) the lower the correlation between the firm’s investment retums and claims costs, 3) for firms which write “longer tail” fines of insurance, and 4) the more the firm concentrates its investments in tax-favored assets. These predictions are tested in an empirical analysis of the reinsurance behavior of U.S. property-liability insurance firms during the period 1980-1987.